2012
DOI: 10.1093/hmg/dds006
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and epigenetic mechanisms collaborate to control SERPINA3 expression and its association with placental diseases

Abstract: SERPINA3 (Serpin peptidase inhibitor clade A member 3), also known as a1-antichymotrypsin, is a serine protease inhibitor involved in a wide range of biological processes. Recently, it has been shown to be up-regulated in human placental diseases in association with a hypomethylation of the 5' region of the gene. In the present study, we show that the promoter of SERPINA3 is transcriptionally activated by three transcription factors (TFs) (SP1, MZF1 and ZBTB7B), the level of induction being dependent on the rs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
71
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(72 citation statements)
references
References 42 publications
1
71
0
Order By: Relevance
“…The reduced expression of SERPINA3 raises a number of atrophy human diseases, including chronic obstructive pulmonary disease, Parkinson’s disease, Alzheimer’s disease, Stroke, Cystic Fibrosis and Cerebral Hemorrhage [6, 9, 10, 20, 21]. ApoA4, an endogenous protein secreted from the intestine as a novel ligand of NR4A1, increases SERPINA3; which implies that ApoA4 may be involved in regulating the above diseases, and can be utilized as a therapy target.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reduced expression of SERPINA3 raises a number of atrophy human diseases, including chronic obstructive pulmonary disease, Parkinson’s disease, Alzheimer’s disease, Stroke, Cystic Fibrosis and Cerebral Hemorrhage [6, 9, 10, 20, 21]. ApoA4, an endogenous protein secreted from the intestine as a novel ligand of NR4A1, increases SERPINA3; which implies that ApoA4 may be involved in regulating the above diseases, and can be utilized as a therapy target.…”
Section: Discussionmentioning
confidence: 99%
“…Its major target is the cathepsin family, a pro-inflammatory enzyme released at sites of inflammation, which contributes to the activation of inflammatory cytokines, the degradation of pathogens, and the remodeling of tissues [8]. Therefore, by inhibiting cathepsin G, SERPINA3 should limit inflammation, coagulation, extracellular matrix remodeling and apoptosis [9]. SERPINA3 has been involved in the pathology of a number of devastating human diseases including Parkinson’s disease and Alzheimer’s disease.…”
Section: Introductionmentioning
confidence: 99%
“…Retarded caruncles showed up-regulation of serpin A3-8 (a1-antichymotrypsin), suggesting a role in placental development in the buffalo. In this regard, serpin A3-8 was upregulated in human placental diseases in association with hypomethylation of the 5 0 region of the gene [80], and its involvement in placental diseases occurs through its strict regulation by a combination of epigenetic, genetic, and transcription-factor mediated pathways [81]. The up-regulation of proteins with protease inhibitor activity in both retarded chorioamnions and retarded caruncles suggests a disequilibrium in proteolytic control that, to date, has only been described as a cause of human pre-eclampsia [82,83].…”
Section: Balestrieri Et Almentioning
confidence: 99%
“…Consequently, progress has been made in identifying global methylation profiles in the PE placenta as several studies have performed methylation arrays [20][22]. Additionally, there are several studies to date that have investigated alterations in gene specific DNA methylation within the PE placenta including SERPINA3 [23], [24], MMP-9 [25], STOX1 [26] and Syncytin-1 [27]. However, only one study has demonstrated that methylation of a placental gene ( CYP24A1 ) can affect placental function, specifically, regulating the level of active vitamin D at the feto-maternal interface [28].…”
Section: Introductionmentioning
confidence: 99%